EFEKTIVITAS SKK MIGAS DALAM MEWUJUDKAN KEMAKMURAN RAKYAT BERDASARKAN PASAL 33 UUD 1945 - Radityo Amaradipta Prasodjo (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to understand and explain whether SKK Migas has been running based on the 1945 Constitution in accordance to Pancasila. This study uses normative legal research methods with data sources in the form of primary and secondary legal materials. The results showed that in the decision of the Constitutional Court Number 36/PUU-X/2012 Law on the replacement of BP Migas by SKK Migas as the manager of the upstream oil and gas sector was considered to violate Article 33 of the 1945 Constitution of the Republic of Indonesia. Article 33 of the 1945 Constitution was the constitutional basis the state especially in the welfare of the people. Unfortunately, accordance with Law Number 22 of 2001 concerning the Implementation of Oil and Gas Business Activities still causes some polemics that need to be solved immediately. As already known about the oil sector, there is a policy of providing subsidies and corporate social responsibility (CSR). This is undoubtedly in accordance with Article 33 of the 1945 Constitution that state control is for the greatest prosperity of the people. SKK Migas as a government representative should be more intensifying about Corporate Social Responsibility (CSR), so that the form of corporate social responsibility to the community and the surrounding environment is fulfilled and achieved based on Pancasila.